Parenting for Lifelong Health: A pragmatic cluster randomised controlled trial of a non-commercialised parenting programme for adolescents and their families in South Africa - Cluver, L; Meinck, F; Steinert, J; Shenderovich, Y; Doubt, J; Herrero Romero, R; Lombard, C; Redfern, A; Ward, C; Tsoanyane, S; Nzima, D; Sibanda, N; et al. (BMJ Publishing Group, 2018)
Objective To assess the impact of ‘Parenting for Lifelong Health: Sinovuyo Teen’, a parenting programme for adolescents in low- and middle-income countries, on abuse and parenting practices. Design Pragmatic cluster randomised control trial. Setting 40 villages/urban sites (clusters) in the Eastern Cape province, South Africa. Participants 552 families reporting conflict with their adolescents (aged 10-18). Intervention Intervention clusters (n=20) received a 14-session parent and adolescent programme delivered by trained community members. Control clusters (n=20) received a hygiene and hand-washing promotion programme. Main outcome measures Primary outcomes: abuse and parenting practices at one and 5-9 months post-intervention. Secondary outcomes: Caregiver and adolescent mental health and substance use, adolescent behavioural problems, social support, exposure to community violence, and family financial wellbeing at 5-9 months post-intervention. Blinding was not possible. Results At 5-9 months post-intervention, the intervention was associated with lower abuse (caregiver report incidence rate ratio (IRR) 0.55 (95% CI 0.40 to 0.75, p<0.001); corporal punishment (caregiver report IRR=0.55 (0.37 to 0.83, p=0.004)); improved positive parenting (caregiver report d=0.25 (0.03 to 0.47, p=0.024)), involved parenting (caregiver report d=0.86 (0.64 to 1.08, p<0.001); adolescent report d=0.28 (0.08 to 0.48, p=0.006)) and less poor supervision (caregiver report d=-0.50 (-0.70 to -0.29, p<0.001); adolescent report d=-0.34 (-0.55 to -0.12, p=0.002)), but not decreased neglect (caregiver report IRR 0.31 (0.09 to 1.08, p=0.066); adolescent report IRR 1.46 (0.75 to 2.85, p=0.264)), inconsistent discipline (caregiver report d=-0.14 (-0.36 to 0.09, p=0.229); adolescent report d=0.03 (-0.20 to 0.26, p=0.804)), or adolescent report of abuse IRR=0.90 (0.66 to 1.24, p=0.508) and corporal punishment IRR=1.05 (0.70 to 1.57, p=0.819) Secondary outcomes showed reductions in caregiver corporal punishment endorsement, mental health problems, parenting stress, substance use and increased social support (all caregiver report). Intervention adolescents reported no differences in mental health, behaviour or community violence, but had lower substance use (all adolescent report). Intervention families had improved economic welfare, financial management, and more violence avoidance planning (in caregiver and adolescent report). No adverse effects were detected. Conclusions This parenting programme shows promise for reducing violence, improving parenting and family functioning in low-resource settings.